2017
DOI: 10.1063/1.4977787
|View full text |Cite
|
Sign up to set email alerts
|

Limited surface mobility inhibits stable glass formation for 2-ethyl-1-hexanol

Abstract: Previous work has shown that vapor-deposition can prepare organic glasses with extremely high kinetic stabilities and other properties that would be expected from liquid-cooled glasses only after aging for thousands of years or more. However, recent reports have shown that some molecules form vapor-deposited glasses with only limited kinetic stability when prepared using conditions expected to yield a stable glass. In this work, we vapor deposit glasses of 2-ethyl-1-hexanol over a wide range of deposition rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
0
12
1
Order By: Relevance
“…As an example, the surface diffusion coefficient of o-terphenyl (OTP), a non HB-molecule, and sorbitol (HB molecule), two molecules with similar sizes, differ by 10 5 at T g [132]. In the same reasoning line, it was shown that molecules forming extensive intermolecular HB, such as polyalcohols, produced glasses of lower kinetic stability compared to non-hydrogen-bonding molecules at the same deposition rate [88,91,93,132].…”
Section: Is Surface Diffusion Responsible For Ultrastable Glass Forma...mentioning
confidence: 93%
“…As an example, the surface diffusion coefficient of o-terphenyl (OTP), a non HB-molecule, and sorbitol (HB molecule), two molecules with similar sizes, differ by 10 5 at T g [132]. In the same reasoning line, it was shown that molecules forming extensive intermolecular HB, such as polyalcohols, produced glasses of lower kinetic stability compared to non-hydrogen-bonding molecules at the same deposition rate [88,91,93,132].…”
Section: Is Surface Diffusion Responsible For Ultrastable Glass Forma...mentioning
confidence: 93%
“…16 In vapor deposition, molecules forming extensive intermolecular HBs (e.g., polyalcohols) have been observed to produce glasses of lower kinetic stability than non-hydrogen-bonding molecules at the same deposition rate 17 and require slower deposition in order to attain the same stability. 18 Qualitative explanations have been proposed for the molecular dependence of surface mobility. 15,16 The size effect is attributed to a steep gradient of mobility beneath the free surface and the deeper penetration of a larger molecule into that gradient.…”
Section: Articlementioning
confidence: 99%
“…Elastomer materials are widely utilized in the fields of electronics, aerospace and military because of their low density, remarkable adaptability, and easy-processing properties, and so forth. However, most of the elastomer materials are strongly influenced by their servicing environment. For example, at the temperature below −125 °C, they experience brittleness and cracking, leading to strong degradations of the elastomeric materials performance.…”
Section: Introductionmentioning
confidence: 99%